2013
DOI: 10.1136/emermed-2013-202719
|View full text |Cite
|
Sign up to set email alerts
|

Unscheduled return visits (URV) in adults to the emergency department (ED): a rapid evidence assessment policy review

Abstract: Unscheduled return visits (URV) to the emergency department (ED) may be an important quality indicator of performance of individual clinicians as well as organisations and systems responsible for the delivery of emergency care. The aim of this study was to perform a rapid evidence assessment policy-based literature review of studies that have looked at URVs presenting to the ED. A rapid evidence assessment using SCOPUS and PUBMED was used to identify articles looking at unplanned returns to EDs in adults; thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 30 publications
4
63
0
3
Order By: Relevance
“…The literature suggests that approximately 3% is a reasonable estimation of the average global return visit rate, but it is apparent that there is a large variation (0.4%–43.9%) 17. Moreover, we have the impression that there may be a disparity in basic aspects, such as excluding from the sample population those patients who will not return to the ED, due to hospitalisation or death.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The literature suggests that approximately 3% is a reasonable estimation of the average global return visit rate, but it is apparent that there is a large variation (0.4%–43.9%) 17. Moreover, we have the impression that there may be a disparity in basic aspects, such as excluding from the sample population those patients who will not return to the ED, due to hospitalisation or death.…”
Section: Discussionmentioning
confidence: 93%
“…Many other factors are known to be involved in the frequency of returns, such as physician experience or situations of overcrowding,2 17 but in the present study we did not examine such variables because they cannot be introduced into the definition of an indicator. In our results, the definition based on a single variable, for example, ‘return visit resulting in admission’ has the advantage of simplicity of concept, but achieves only 45% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…These may include multidisciplinary assessment areas or wards, or enhanced geriatric outreach services that aim to prevent unplanned hospital readmissions. Jelinek et al 6 in a study of adult frequent attendees in Perth showed that moderately frequent attendees (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) presentations per year) were more urgent compared with the 'average' ED patient. This was consistent with the findings of the present study and supported by the higher admission rate observed in this group of patients but also reflects the observation that the age specific rates of frequent representations were still highest in the elderly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These observations in conjunction with the lower in-patient admission rate in this group suggested that improved community case management in areas of mental health and drug and alcohol services as well as including primary care coordination and education 14 may help to prevent unplanned ambulance use and representations to ED and supports the need for improved continuity and access to care for those with mental illness. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…Maternal immigrant status was used to identify children included in the study to reflect the influence of family immigrant status, rather than that of only the child. Maternal immigrant status has been previously associated with risk of injury 14. Records with a missing or invalid health card number, age or sex were excluded.…”
Section: Methodsmentioning
confidence: 99%